2020
DOI: 10.21203/rs.3.rs-24044/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prevalence of some virulence genes and antibiotic susceptibility pattern of Pseudomonas aeruginosa isolated from different clinical specimens

Abstract: Background: Pseudomonas aeruginosa is an opportunistic human pathogen and are reported to cause acute and chronic infectious diseases. Due to its high ability to acquire resistance to many antibiotics, it has become a global public health threat. It consists of some virulence genes that may lead to its pathogenicity. The main objective of this cross-sectional study was to detect the virulence genes and antibiotic susceptibility pattern of P. aeruginosa isolated from clinical specimens collected from government… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 10 publications
4
3
0
Order By: Relevance
“…showed resistance to ciprofloxacin that is comparable to studies of Anil and Shahid (2013), and Ramana and Chaudhury (2012) that showed 27.59 % and 39% resistant to ciprofloxacin, respectively. The result is also comparable to recent studies of Agbo et al (2020), Chand et al (2020) and Kumar et al (2020) which showed 21.68 %, 31.03 %, and 35.55 % resistant to ciprofloxacin, respectively, suggesting it could be the regular regimen for Pseudomonas spp infection.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…showed resistance to ciprofloxacin that is comparable to studies of Anil and Shahid (2013), and Ramana and Chaudhury (2012) that showed 27.59 % and 39% resistant to ciprofloxacin, respectively. The result is also comparable to recent studies of Agbo et al (2020), Chand et al (2020) and Kumar et al (2020) which showed 21.68 %, 31.03 %, and 35.55 % resistant to ciprofloxacin, respectively, suggesting it could be the regular regimen for Pseudomonas spp infection.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are also similar to the findings of Chand et al (2020) indicating higher sensitivity of gentamycin with a resistant rate of only 20.68 %. The result is not consistent with the findings of Agbo et al (2020) and Motbainor et al (2020) since they reported that for Pseudomonas the resistance rate against gentamycin was high i.e.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Yamuna Chand, Sujan Khadka, and Sanjeep Sapkota share the first authorship. A preprint of the current study has previously been published [50].…”
Section: Abbreviationsmentioning
confidence: 99%